Legality of Community Agricultural Activities in Forest Areas based on Constitutional Court Decision Number 181/Puu-Xxii/2024 - Sasongko, Taufan Fajar; Al'anam, Muklis; Baihaki, Ahmad (JURNAL AKTA, 2025)
Constitutional Court Decision Number 181/PUU-XXII/2024 opens up legal space for communities living in forest areas to engage in plantation activities, thereby creating new dynamics in Indonesia's forestry legal regime. This ruling has sparked debate because, on the one hand, it strengthens the protection of constitutional rights of the community, but on the other hand, it raises concerns about environmental sustainability and forest area governance. This study aims to analyse the legal implications of the ruling and the challenges of its implementation within the framework of forestry administrative law. This study uses a normative legal research method with a legislative and conceptual approach. The results of the study show that Constitutional Court Decision Number 181 / PUU-XXII / 2024 marks a paradigm shift in forestry management from a repressive approach to a more inclusive and equitable approach, emphasising the principles of proportionality, legal certainty, and recognition of the social reality of the community. However, the implementation of this decision faces serious challenges, particularly related to regulatory disharmony, limited administrative capacity, and the risk of environmental degradation. Therefore, forestry administration law reform is needed that emphasises the principles of legality, good governance, control of discretion, and integration of sustainable development principles so that the protection of community rights and forest conservation can be balanced.